Controlled delivery of membrane proteins to artificial lipid bilayers by nystatin-ergosterol modulated vesicle fusion. - de Planque, MR; de Planque, MR; Mendes, G; Zagnoni, M; Sandison, M; Fisher, K; Berry, R; Watts, A; Morgan, H (2006)
The study of ion channels and other membrane proteins and their potential use as biosensors and drug screening targets require their reconstitution in an artificial membrane. These applications would greatly benefit from microfabricated devices in which stable artificial lipid bilayers can be rapidly and reliably formed. However, the amount of protein delivered to the bilayer must be carefully controlled. A vesicle fusion technique is investigated where composite ion channels of the polyene antibiotic nystatin and the sterol ergosterol are employed to render protein-carrying vesicles fusogenic. After fusion with an ergosterol-free artificial bilayer, the nystatin-ergosterol channels do not dissociate immediately and thus cause a transient current signal that marks the vesicle fusion event. Experimental pitfalls of this method were identified, the influence of the nystatin and ergosterol concentration on the fusion rate and the shape of the fusion event marker was explored, and the number of different lipid species was reduced. Under these conditions, the -amyloid peptide could be delivered in a controlled manner to a standard planar bilayer. Additionally, electrical recordings were obtained of vesicles fusing with a planar lipid bilayer in a microfabricated device, demonstrating the suitability of nystatin-ergosterol modulated vesicle fusion for protein delivery within microsystems.